Legal Protection for Creators Against Copyright Songs Reprised by Cover Song Musicians in Royalty Payments - Kristian, Rio Nanda; Anynoegroho, Anynoegroho; Jalianery, Joanita (Journal of Law, Politic and Humanities, 2025)
This research is motivated by legal vagueness in Article 87 paragraph (1) of Law No. 28 of 2014 concerning Copyright. Article 87 paragraph (1) stipulates that the author of the work, the copyright owner, or other related parties, is entitled to obtain financial compensation for the commercial use of their work by becoming a member of the Collective Management Institution. This situation raises legal issues, especially for independent musicians who do not join the Collective Management Institution (LMK), especially when their works are used as cover songs and disseminated through social media without permission. The imbalance in the protection of creators' economic rights becomes the main issue. This study uses normative juridical method with theoretical and regulatory approaches supported by literature sources. The findings show that creators have the right to legal protection, both for their moral interests and economic aspects. Copyright is a right that arises automatically in the work created by the creator, this right is given exclusively in the form of moral and economic rights without reducing the restrictions on the creator of the results of ideas and hard work, the work must be realized and declared. Therefore, in order to overcome the legal vagueness of Article 87 of Law No. 28 of 2014. So it is necessary to review Article 87 of Law No. 28 of 2014 on Copyright the owner of the work, the owner of the related rights, and who holds the copyright that has not been registered as a member of the Collective Management can still obtain economic rights from their work so that the collective system and royalty distribution mechanism can be applied fairly to all creators, including those who are not members of the Collective Management Institution